Good garden bugs : everything you need to know about beneficial predatory insects - Gardiner, Mary M. (Quarry Books, 2015)
Aphids, ants, grubs, and earwigs are not only creepy-crawlies but they can wreak havoc on your garden and new plants. But fear not! You don't need dangerous chemicals in fertilizers and pesticides to enjoy a lively, healthy garden. The secret? More lady beetles, fewer aphids! Wildlife in your garden--especially insects--can be natural pesticide alternatives, they can pollinate plants, they can contribute important nutrients to the soil, and sometimes they're simply beautiful to look at. This book will discuss how to attract them, how to preserve the natural habitats they need, and how to work with them to grow and enjoy your garden.